Faktor Yang Berhubungan dengan Kelelahan Kerja Pada Petani - Ade Wira Lisrianti Latief; Sri Novianti Bahar; Rizky Maharja; Rostati Rostati; Muhammad Irsyad (Sarana Ilmu Indonesia (salnesia), 2022)
Fatigue is a common complaint experienced by the working community. The term fatigue usually denotes a different condition for each individual, but all of them lead to a loss of efficiency and a decrease in work capacity and endurance. Fatigue is classified into two types namely, muscle fatigue and general fatigue. The purpose of this study was to determine the factors associated with work fatigue in farmers in Amessangngeng Village, Donri-Donri District, Soppeng Regency. This study used a quantitative research method with a cross-sectional approach. The population of this study was farming groups in Ammessangeng Village, Donri-Donri District, Soppeng Regency with 43 farmers. This study used total sampling. The results showed that there was a relationship between age (p-value=0,024), length of work (p=0,026), years of service (p-value=0,008), and work attitude (p-value=0,013) with fatigue among farmers. It is hoped that farmers will pay more attention to their lifestyle and work methods so that when they work they do not experience work fatigue.